The Impact of Transportation Infrastructure on Community Economic Development - Syahril Nasution (Yayasan Bayt Shufiya Nusantara, 2025)
Transportation infrastructure is a fundamental catalyst for improving regional economic productivity and enhancing societal welfare. This study analyzes the impact of road infrastructure development on community economic conditions in Air Hitam Village, Kualuh Leidong District, North Labuhanbatu Regency, Indonesia. A quantitative approach was employed using a structured survey of 60 respondents selected through stratified random sampling. Data were analyzed using SPSS Version 22 with linear regression techniques. The findings reveal that road infrastructure has a significant and positive influence on the local economy, as evidenced by the t-value (40.353) exceeding the critical t-table value (1.671). Improved accessibility strengthens market participation, increases income opportunities, and supports rural economic diversification. The study emphasizes that transportation development must be complemented by inclusive policies to ensure equitable distribution of economic benefits.